Effect of Cooking Time on Physical Properties of Almond Milk-Based Lemak Cili Api Gravy - Saruan, Nurathirah; Abdullah, Norazlin; Muhammad, Norhayati; A. Talip, Balkis (Journal of Science and Technology, 2018)
One of the crucial elements in developing or reformulating product is to maintain the quality throughout its entire shelf life. This study aims to determine the effect of different cooking time on the almond milk-based of lemak cili api gravy. Various cooking times of 5, 10, 15, 20, 25 and 30 minutes were employed to the almond milk-based lemak cili api gravy followed by determination of their effects on physical properties such as total soluble solids content, pH and colour. pH was determined by using a pH meter. Refractometer was used to evaluate the total soluble solids content of almond milk-based lemak cili api gravy. The colours were determined by using spectrophotometer which expressed as L*, a* and b* values. Results showed that almond milk-based lemak cili api gravy has constant values of total soluble solids with pH range of 5 to 6, which can be classified as low acid food. Colour analysis showed that the lightness (L*) and yellowness (b*) are significantly increased while redness (a*) decreased. Â In conclusion, this study shows that physical properties of almond milk-based lemak cili api gravy changes by increasing the cooking time.